(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Sitagliptin is a commonly prescribed anti-diabetic drug that has been authorized for the treatment of Type 2 diabetes patients. Sitagliptin is a selective inhibitor of the dipeptidyl peptidase-4 enzyme. Accurate and exact measurement is essential for determining sitagliptin’s pharmacokinetics, bioavailability, and therapeutic effectiveness. A variety of analytical methods have been developed for the measurement of Sitagliptin, over time, each with specific benefits and drawbacks. With the help of high-performance liquid chromatography, high-performance thin layer chromatography, liquid chromatography-mass spectrometry, spectroscopy (ultraviolet visible spectroscopy), electroanalytical methods, and ultraviolet performance liquid chromatography methods, this critical review aims to comprehensively evaluate the various analytical techniques used for sitagliptin quantification. The overview covers each technique’s fundamental guiding concepts, sample preparation steps, and detection methods. Based on publicly available data, each method’s performance qualities, including sensitivity, selectivity, accuracy, precision, and linearity, are evaluated rigorously. It is also explored whether these methods can be used on complicated biological matrices, including plasma, serum, and urine. The overview is concluded with a comparison of the various analytical approaches, highlighting their advantages and disadvantages. In addition, information on new developments and trends in sitagliptin measurement techniques is included.